Influence of MHC on genetic diversity and testicular expression of linked olfactory receptor genes - Mingue Kang; Byeongyong Ahn; Jae Yeol Shin; Hye-Sun Cho; Jongan Lee; Chankyu Park (BMC Genomics)
Abstract Background Olfactory receptor (OR) genes are highly polymorphic and form extensive families that recognize a wide range of vertebrate odorants. To explore the genetic diversity of MHC-linked OR genes and their connection to MHC genes, we conducted a combined haplotype analysis of MHC-linked OR and MHC class I genes to determine the influence of MHC on OR diversity, which could be associated with MHC-based mate selection. Results We selected nine MHC-linked OR genes based on their expression levels in pig testes and developed a sequence-based typing method for these genes. We then performed high-resolution typing of these OR genes, along with three major classical MHC class I genes (SLA-1, -2, and − 3), in 48 pigs across six breeds. We observed significantly higher allelic diversity (P < 0.01) in ORs with strong linkage disequilibrium (LD) to SLA compared to those with weak or no LD, and we identified 48 SLA class I-OR haplotypes using the expectation-maximization algorithm. The genetic diversity of SLA-linked ORs was positively correlated with their expression levels in the testis. Specifically, SLA-linked ORs with higher testicular expression (FPKM ≥ 0.1) exhibited an increase in the number of codons under mutually diversifying selection with SLA compared to those with lower expression (FPKM < 0.1). Conclusions The presence of evolutionary interactions between MHC and linked OR genes supports the potential involvement of MHC-linked ORs in MHC-based mate selection. The use of combined haplotype information for MHC and linked ORs could provide new insights into the reproductive biology of animals.